2017
DOI: 10.1080/09658211.2017.1404110
|View full text |Cite
|
Sign up to set email alerts
|

The impact of own and others’ alcohol consumption on social contagion following a collaborative memory task

Abstract: When one person alters his or her recollection of an event to be consistent with another person's erroneous account of the same event, social contagion has occurred. In two studies, we examined whether alcohol consumption influences the degree to which people engage in social contagion. In Study 1, participants consumed alcohol, an alcohol placebo, or a soft drink and then completed a collaborative recall test with a confederate who consumed a soft drink. In Study 2, participants consumed a soft drink and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 53 publications
(93 reference statements)
1
14
1
Order By: Relevance
“…Schreiber Compo et al () sought to use the hypervigilance hypothesis to explain increased DK responding in placebo participants but did not find that consumption of a placebo influenced correct memory performance. This is in line with other research that failed to find superior performance in placebo participants (Crossland et al, ; Schreiber Compo et al, ; Thorley & Christiansen, ; Yuille & Tollestrup, ). The present research sought to further explore alcohol expectancy effects by using a fully balanced placebo design.…”
Section: Memory and Alcohol‐related Theoretical Frameworksupporting
confidence: 91%
See 1 more Smart Citation
“…Schreiber Compo et al () sought to use the hypervigilance hypothesis to explain increased DK responding in placebo participants but did not find that consumption of a placebo influenced correct memory performance. This is in line with other research that failed to find superior performance in placebo participants (Crossland et al, ; Schreiber Compo et al, ; Thorley & Christiansen, ; Yuille & Tollestrup, ). The present research sought to further explore alcohol expectancy effects by using a fully balanced placebo design.…”
Section: Memory and Alcohol‐related Theoretical Frameworksupporting
confidence: 91%
“…The majority of lab‐based studies have found that alcohol intoxication does not affect recall accuracy (Crossland, Kneller, & Wilcock, ; Hagsand, Roos af Hjelmsäter, Granhag, Fahlke, & Söderpalm Gordh, , ; Hildebrand Karlén, Roos af Hjelmsäter, Fahlke, Granhag, & Söderpalm Gordh, , ; La Rooy, Nicol, & Terry, ; Schreiber Compo et al, ). Some studies have shown that as alcohol dosage increases, recall quantity decreases (Altman, Schreiber Compo, McQuiston, Hagsand, & Cervera, ; Flowe, Takarangi, Humphries, & Wright, ; Hagsand et al, ; Hildebrand Karlén et al, ; Thorley & Christiansen, ; Yuille & Tollestrup, ), whereas other studies failed to show an effect of alcohol on recall completeness (Crossland et al, ; LaRooy et al, ; Schreiber Compo et al, ). In addition to dosage, other important factors to consider are recall format and gender.…”
Section: Alcohol and Eyewitness Event Recallmentioning
confidence: 99%
“…Moreover, during collaborative discussion, group members may introduce information that is inaccurate. A number of studies have demonstrated that such inaccurate contributions often go undetected and become encoded by group members and used on subsequent tasks, resulting in an effect called the social contagion of memory (Andrews & Rapp, 2014; Davis & Meade, 2013; Roediger, Meade, & Bergman, 2001; Thorley & Christiansen, 2018).…”
Section: What Is Collaborative Problem Solving?mentioning
confidence: 99%
“…Their finding, however, must be treated with caution as alcohol consumption was a binary yes/no variable, meaning the volume consumed, and its impact upon age estimation accuracy, was not considered. High levels of intoxication during an event can impair recollection of it (Read, Yuille, & Tollestrup, 1992;Thorley & Christiansen, 2018;Van Oorsouw & Merckelbach, 2012;Van Oorsouw, Merckelbach, & Smeets, 2015), although the ability to remember faces is often unaffected (see Altman, Schreiber Compo, McQuiston, Hagsand & Cervera, In Press). Whether or not high levels of intoxication can impair sexual assault victims' ability to recollect offenders' ages is unknown but warrants examination.…”
Section: Offence-specific Factors and Age Estimation Accuracymentioning
confidence: 99%